ECOTHEOLOGY IN RELIGIOUS TEXTS: ISLAMIC, CHRISTIAN, HINDU, AND BUDDHIST PERSPECTIVES ON RESPONDING TO THE ENVIRONMENTAL CRISIS - Rusmiati, Elis Teti; Maryasih, Ni Luh Kerti; Hutasoit, Binsar Mangaratua; Widoyo, Heru (Universitas prof. Dr. Moestopo (Beragama), 2023)
The global environmental crisis demands solutions that are not only rooted in science and policy but also address spiritual and ethical dimensions. Various religious traditions emphasize human responsibility in maintaining ecological balance. This study explores the concept of ecotheology within religious texts—Islam, Christianity, Hinduism, and Buddhism—to understand how religious values can synergize in responding to environmental challenges. Using a religious hermeneutic approach, this research analyzes verses from the Qur'an, the Bible, the Vedas, and the Tripitaka that discuss the human-nature relationship. The findings reveal that all four religions share fundamental principles that emphasize ecological balance, such as the concept of khalifah in Islam, stewardship in Christianity, karma and ahimsa in Hinduism, and the interdependence of living beings in Buddhism. The synergy of these values can serve as an ethical foundation for faith-based environmental movements and sustainable policies. Furthermore, this study examines the role of religious institutions in promoting ecological awareness through education, preaching, and social action. It recommends efforts to reinterpret religious texts to be more contextual to modern ecological challenges and to encourage interfaith collaboration in environmental advocacy. Thus, ecotheology can serve as a multidisciplinary approach that integrates religion, ethics, and ecosystem sustainability in contemporary society.